A nanocarbon / sulfur / graphene / terbium composite positive electrode and its preparation method and a high-performance lithium-sulfur battery using the same
By using nanocarbon/sulfur/graphene/terbium composite positive electrode in lithium sulfur batteries and using Tb3+/Tb4+ composite as terbium components, the multi-electron and multiphase sulfur redox reaction and soluble lithium polysulfide in lithium sulfur batteries are solved. The accumulation and shuttle problems significantly improve the cycle stability and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202210852361.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-07-19
AI Technical Summary
Due to the accumulation and shuttle of complex multi-electron, multi-phase sulfur redox reactions (SRRs) and soluble lithium polysulfide (LiPSs), lithium sulfur batteries have slow charge transfer mobility mechanics, affecting the commercial application of batteries.
Nanocarbon/sulfur/graphene/terbium composite positive electrode was used, graphene-terbium composite material was used as the positive electrode modification layer and CNTs-S composite material was used as the positive electrode sheet, and Tb3+/Tb4+ composite was combined as the terbium component, and ultrasonic treatment and heat treatment were used. The composite material was prepared by the same method to form a new electronic memory with spontaneous electron loss and capture capabilities.
The initial discharge specific capacity of lithium sulfur batteries at 0.2 C reaches 1522 mAh g-1, and can cyclize 500 turns at 1 C, with a single-turn capacity decay rate of 0.087%, which significantly improves the cycle stability of the battery and Electrochemical properties.
Smart Images

Figure CN115172699B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of battery positive electrode materials, in particular to a nano-carbon / sulfur / graphene / terbium composite positive electrode and a preparation method thereof, and a high-performance lithium-sulfur battery using the same. Background Art
[0002] The increasing demand for high-quality electric vehicles and mobile electronics has prompted researchers to develop advanced energy storage systems with higher energy and power density than current lithium-ion batteries. Among potential candidates, lithium-sulfur batteries are expected to reach 1672 mAh g -1 Weight capacity and 2600 Wh kg -1 The energy density of lithium-sulfur batteries is very high, and they have great application prospects in the next generation of energy storage. However, due to the complex multi-electron and multi-phase sulfur redox reactions (SRR) in lithium-sulfur batteries, they usually lead to slow charge transfer kinetics and the accumulation and shuttling of soluble lithium polysulfides (LiPSs) in the working battery. These are problems that must be solved for the commercialization of lithium-sulfur batteries.
[0003] Rare earth elements are considered to be promising electron storage (electron source and electron drain) due to their partially unfilled electron configuration. Rare earth oxides have rich electronic structures, variable valence states and coordination numbers, and are indispensable in the simultaneous catalysis of complex multi-electron reaction systems (such as catalytic automobile exhaust purification, including HC / CO oxidation reactions and NO reduction reactions). Among the 17 rare earth elements, only terbium (Tb) has the characteristics of rich valence states, strong oxidizing properties and no radioactivity. Normally, 4 f Tb with 8 electrons is in the +3 oxidation state (Tb 3+ ), which can be used as an electron source to easily provide electrons to external species. +4 oxidation state of Tb (Tb 4+ ) contains half-filled 4 f The shell, like an electron drain, gives Tb more possibilities for electron gain. 4+ With high oxidation capacity and high redox potential of 3.3 V vs. NHE, it can be used as a potential oxidant for sulfur oxidation reaction during charging. 3+ and Tb 4+ Inspired by their respective advantages, we believe that using Tb 3+ / Tb 4+ The complex is feasible for developing a new type of electronic memory with spontaneous electron loss and capture capabilities. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a nano-carbon / sulfur / graphene / terbium composite positive electrode and a high-performance lithium-sulfur battery using the same.
[0005] The present invention provides a nano-carbon / sulfur / graphene / terbium composite positive electrode, comprising a graphene-terbium composite material as a positive electrode modification layer and a CNTs-S composite material as a positive electrode sheet; preferably, the "terbium" comprises Tb 3+ , Tb 4+ , Tb 3+ / 4+ (In this application document, Tb 3+ Refers to Tb molecules, for example: tris(acetylacetonato)(1,10-phenanthroline)terbium(III) molecule; Tb 4+ Refers to tetravalent terbium oxide; Tb 3+ / 4+ Refers to a trivalent and tetravalent mixed terbium oxide. ) The most preferred terbium is Tb 3+ / 4+ .
[0006] The preparation method of the composite positive electrode comprises the following steps:
[0007] Step (1), graphene and Tb 3+ (i.e., Tb molecules) are dispersed in anhydrous ethanol at a mass ratio of 1-15:1 and subjected to ultrasonic treatment. After the ultrasonic treatment, the two substances are stirred to mix evenly. Step (2), drying the mixed solution obtained in step (1) to obtain graphene-Tb 3+ The composite catalyst is placed in a tube furnace for heat treatment for half an hour, and a graphene-terbium oxide composite material containing terbium of different valence states can be obtained by adjusting the gas environment; step (3) uses a typical melt-diffusion method to prepare a CNTs-S composite material; the specific operation is: CNTs and sulfur powder are mixed in a ratio of 1:4 The mixture is then stirred at room temperature, air-dried until CS2 is completely evaporated, and then heated for a period of time and cooled to room temperature, and then ground to obtain a CNTs-S composite material; the CNTs-S composite material, a binder, and a conductive additive are mixed and dispersed in an organic solvent at a mass ratio of 8:1:1, and coated on an aluminum foil and placed in an oven for drying to obtain a positive electrode sheet; step (4), uniformly dispersing the graphene-terbium composite material in an organic solvent, performing ultrasonic treatment, and coating it on the dried positive electrode sheet prepared in step (3), and then continuing to dry in an oven to obtain a graphene-terbium composite material interlayer; step (5), inserting a layer of the graphene-terbium composite material interlayer prepared in step (4) on the upper layer of the dried positive electrode sheet obtained in step (3), and finally cutting it into a required shape and size to obtain a nano-carbon / sulfur / graphene / terbium composite positive electrode.
[0008] Preferably, in step (1), graphene and Tb 3+ (i.e., Tb molecules) in a mass ratio of 10:1; in step (2), the temperature of the tube furnace is 280-320°C, and the graphene-Tb is obtained in an air environment. 3+ / 4+; In step (3), the heating conditions for cooling to room temperature after reheating for a period of time are: heating at 150-160°C for 10-14 hours; the sulfur content of the CNTs-S composite material is controlled at 75-80 wt%; the binder is polyvinylidene fluoride, and the organic solvent is N-methylpyrrolidone; in step (4), the organic solvent is N-methylpyrrolidone; the drying temperature of the oven is 50-60°C; in step (5), the sulfur loading in the composite positive electrode is controlled at 1-1.2 mg cm −2 .
[0009] Also provided is a high-performance lithium-sulfur battery, comprising the above-mentioned nano-carbon / sulfur / graphene / terbium composite positive electrode.
[0010] The beneficial effects of the present invention are as follows: The present invention provides a terbium supported on a graphene conductive substrate as a positive electrode modification layer to activate continuous SRR in lithium-sulfur chemistry. The high-performance lithium-sulfur battery prepared using the positive electrode has an initial discharge specific capacity of up to 1522 mAh g at 0.2 C. -1 It can stably cycle 500 cycles at 1 C, and the single-cycle capacity decay rate is 0.087%, showing good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0012] Figure 1 , Gh-Tb 3+ , Gh-Tb 3+ / 4+ and Gh-Tb 4+ A top view of the structural model;
[0013] Figure 2 , Gh-Tb x+ (x = 3, 4, 3+ / 4+) Tb f Density of states of the orbital;
[0014] Figure 3 , based on DFT calculation of Li2S n (n = 8, 6, 4, 2, 1) and Gh-Tb 3+ , Gh-Tb 3+ / 4+ , Gh-Tb 4+Side view and binding energy of the optimized structural model between and Gh substrate. The light blue, brown, purple, red, yellow, and green balls represent N, C, Tb, O, S, and Li atoms, respectively;
[0015] Figure 4 , (a) Li2S n (n = 8, 6, 4, 2, 1) and Gh-Tb 3+ , Gh-Tb 3+ / 4+ , Gh-Tb 4+ Adsorption energy between Gh and substrate. (b) Gibbs free energy change of sulfur reduction process on the surface of four catalysts;
[0016] Figure 5 , (a) Molecular structure of tris(acetylacetonate)(1,10-phenanthroline)terbium(III). (b) Thermogravimetric curve of tris(acetylacetonate)(1,10-phenanthroline)terbium(III) molecule;
[0017] Figure 6 , Gh-Tb x+ Schematic diagram of the synthesis process of the (x = 3, 4, 3 + / 4+) composites;
[0018] Figure 7 , Gh-Tb x+ (a) Tb 3 for (x = 3, 4, 3+ / 4+) d XPS spectra and (b) N 1 s XPS spectra;
[0019] Figure 8 , (a, b) Gh-Tb 3+ , (c, d) Gh-Tb 4+ and (e,f)Gh-Tb 3+ / 4+ TEM images of the composite materials;
[0020] Fig. 9 , Gh-Tb 3+ / 4+ Aberration-corrected high-angle annular dark-field scanning transmission electron microscopy image of the composite, where atomically dispersed Tb on Gh appears as bright spots.
[0021] Fig.10 , Gh-Tb 3+ / 4+ EDS elemental mapping of C, N, O and Tb in the composite material;
[0022] Fig.11 , Gh-Tb 3+ / 4+ Full XPS spectrum of composite materials;
[0023] Fig.12 , Gh-Tb3+ / 4+ Cross-sectional SEM image of CNTs-S cathode modified with intermediate layer;
[0024] Fig.13 , (i) without Gh, (ii) with Gh, (iii) with Tb molecules, (iv) with Gh / Tb 3+ / 4+ Photo of Li2S6 solution;
[0025] Fig.14 , Gh and Gh-Tb 3+ / 4+ (a) N2 adsorption-desorption isotherm; (b) pore size distribution;
[0026] Fig.15 , (a) Gh-Tb 3+ / 4+ High-resolution Tb 3 before and after adsorption of Li 2 S 6 d XPS spectra. (b) Gh and Gh-Tb 3 + / 4+ High-resolution S 2 after interaction with Li 2 S 6 p XPS spectra. (c) Gh and Gh-Tb 3+ / 4+ High-resolution Li 1 after interaction with Li2S6 s XPS spectrum;
[0027] Fig.16 , (a) Li2S6 electrolyte as active component, CNTs / Gh-Tb x+ Symmetric cells with (x = 3, 4, 3+ / 4) and CNTs / Gh as electrodes at 30 mV s -1 CV curves of CNTs / Gh-Tb x+ (c) The gray, blue, yellow, and red areas represent the reduction of Li2S8 and Li2S6 on CNTs / Gh, CNTs / Gh-Tb, and CNTs / Gh-Tb cathodes. 3+ 、CNTs / Gh-Tb 4+ and CNTs / Gh-Tb 3+ / 4+ Time-current curve of Li2S decomposition on the positive electrode. The light yellow area represents the oxidation of Li2S6; the gray, blue, yellow and red areas represent the decomposition of Li2S;
[0028] Fig.17 , with Li2S6 electrolyte as active ingredient, CNTs / Gh, CNTs / Gh-Tb 3+ 、CNTs / Gh-Tb 4+ and CNTs / Gh-Tb 3+ / 4+ Nyquist diagram of a symmetric cell with electrodes;
[0029] Fig.18 , (a) CNTs-S / Gh-Tb 3+ / 4+ PITT spectra of (a) CNTs-S / Gh-Tb and CNTs-S / Gh cathode at 2.3-1.9 V with an interval voltage of 0.02 V. x+ (x = 3, 4, 3+ / 4) and CNTs-S / Gh cathode (current pulse: 83.7 mAg -1 GITT charge-discharge curves of the second cycle (10 minutes pulse and 2 hours relaxation). (c) The charge-discharge curves of the four electrodes during the discharge process. D Li + ;
[0030] Fig.19 , CNTs-S / Gh-Tb 3+ / 4+ Nyquist plots of the positive electrode at different discharge voltages and temperatures, with ai at 2.8, 2.6, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, and 1.7 V, respectively;
[0031] Fig. 20 , CNTs-S / Gh-Tb 4+ Nyquist plots of the positive electrode at different discharge voltages and temperatures, with ai at 2.8, 2.6, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, and 1.7 V, respectively;
[0032] Fig.21 , CNTs-S / Gh-Tb 3+ Nyquist plots of the positive electrode at different discharge voltages and temperatures, with ai at 2.8, 2.6, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, and 1.7 V, respectively;
[0033] Fig. 22 , Nyquist plots of CNTs-S / Gh cathode at different discharge voltages and temperatures, where ai is 2.8, 2.6, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, and 1.7 V, respectively;
[0034] Fig.23 , CNTs-S / Gh-Tb 3+ / 4+ Nyquist plots of the positive electrode at different charging voltages and temperatures, with ai at 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, 2.4, 2.6, and 2.8 V, respectively;
[0035] Fig.24 , CNTs-S / Gh-Tb 4+Nyquist plots of the positive electrode at different charging voltages and temperatures, with ai at 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, 2.4, 2.6, and 2.8 V, respectively;
[0036] Fig.25 , CNTs-S / Gh-Tb 3+ Nyquist plots of the positive electrode at different charging voltages and temperatures, with ai at 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, 2.4, 2.6, and 2.8 V, respectively;
[0037] Fig.26 , Nyquist plots of CNTs-S / Gh cathode at different charging voltages and temperatures, where ai is 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, 2.4, 2.6, and 2.8 V, respectively;
[0038] Fig. 27 , according to the Arrhenius equation Figure 19-26 The linear relationship between the logarithm of the charge transfer resistance and the reciprocal of the absolute temperature;
[0039] Fig.28 , used for fitting Figure 19-26 Equivalent circuit of EIS data;
[0040] Fig.29 , (a) Distribution of activation energy during SRR of four electrodes during discharge and (b) charge;
[0041] Fig.30 , (a) CNTs-S / Gh-Tb 3+ / 4+ , (b) CNTs-S / Gh-Tb 4+ , (c) CNTs-S / Gh-Tb 3+ and (d) semi-in-situ S2 of CNTs-S / Gh electrode after discharge and charge to a specific potential. p XPS spectra;
[0042] Fig.31 , (a) CNTs / Gh-Tb 3+ / 4+ , (b) CNTs / Gh-Tb 4+ , (c) CNTs / Gh-Tb 3+ and (d) in situ UV-visible absorption spectra of the CNTs / Gh electrode during discharge in Li2S8 solution;
[0043] Fig.32 , (a) CNTs / Gh-Tb 3+ / 4+ , (b) CNTs / Gh-Tb 4+, (c) CNTs / Gh-Tb 3+ and (d) in situ UV-visible absorption spectra of the CNTs / Gh electrode during the charging process in Li2S3 solution;
[0044] Fig.33 , (ac) discharge and (df) charge of CNTs / Gh-Tb 3+ / 4+ 、CNTs / Gh-Tb 4+ 、CNTs / Gh-Tb 3+ and normalized in situ UV-visible absorption spectra of CNTs / Gh in Li2S8 / Li2S3 solutions;
[0045] Fig.34 , LiPSs conversion pathways on different cathodes. (a, b) CNTs-S / Gh, (c, d) CNTs-S / Gh-Tb during discharge 3+ 、(e,f)CNTs-S / Gh-Tb 4+ and (g,h)CNTs-S / Gh-Tb 3+ / 4+ In-situ Raman spectra of the electrode and the corresponding intensity change curve;
[0046] Fig.35 , Thermogravimetric curves of carbon nanotube-sulfur composites;
[0047] Fig.36 The CNTs-S / Gh-Tb with different mass ratios of Gh to Tb molecules were studied at 1:1, 3:1, 5:1, 10:1 and 15:1. 3+ / 4+ The rate performance of the electrode;
[0048] Fig.37 , (a) CNTs-S / Gh-Tb 3+ / 4+ , (b) CNTs-S / Gh-Tb 4+ , (c) CNTs-S / Gh-Tb 3+ and (d) CV curves of the first four cycles of the CNTs-S / Gh cathode battery between 1.6 and 2.8 V at a scan rate of 0.1 mV s -1 ;
[0049] Fig.38 , (a) CNTs-S / Gh-Tb 3+ / 4+ 、CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3+ and CNTs-S / Gh cathode at 0.1 mV s -1 CV curves at potentials between 1.6 and 2.8 V. (b) Polarization voltage comparison (ΔV is given by Fig.38The voltage value at P3 in a is subtracted from the voltage value at P2);
[0050] Fig.39 , (a) CNTs-S / Gh-Tb 3+ / 4+ , (b) CNTs-S / Gh-Tb 4+ , (c) CNTs-S / Gh-Tb 3+ and (d) Nyquist curves of CNTs-S / Gh electrode before and after 20 cycles;
[0051] Fig.40 , in the first cycle (a) CNTs-S / Gh-Tb 3+ / 4+ and (b) Nyquist curves of CNTs-S / Gh electrode at different (a, b) discharge and (c, d) charge states. R of the two electrodes at different (e) discharge and (f) charge states e value;
[0052] Fig.41 ,from Fig.38 Tafel slopes of the reduction and oxidation processes obtained from the CVs in a, corresponding to (a) P1, (b) P2, and (c) P3;
[0053] Fig.42 , CNTs-S / Gh-Tb 3+ / 4+ 、CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3+ and the galvanostatic charge-discharge curves of the first cycle of CNTs-S / Gh battery at (a) 0.5 C, (b) 1 C, (c) 1.5 C, and (d) 2 C;
[0054] Fig.43 , (a) CNTs-S / Gh-Tb 3+ / 4+ 、CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3+ and the constant current discharge / charge platform curves of CNTs-S / Gh cathode at 0.2 C. (b) Fig.43 a Comparison of the polarization voltage (ΔE, the voltage difference between the charge and discharge platforms) of the four positive electrodes obtained from the constant current charge and discharge curves. (c) Fig.43 The Q obtained from the constant current charge-discharge curve in a up and Q low Capacity value;
[0055] Fig.44 , CNTs-S / Gh-Tb 3+ / 4+ 、CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb3+ and the rate performance between 0.2C and 2C for CNTs-S / Gh cathode;
[0056] Fig.45 , long cycle performance at (a) 1 C and (b) 0.5 C (sulfur content: 1.0 mg cm -2 (c) Long-term cycling performance at 0.1 C (sulfur content: 4.1 mg cm -2 (d) Long-term cycling performance at 0.05 C after three cycles of activation at 0.02 C (sulfur content: 5.2 mg cm -2 , E / S ratio was 7.5 μL mg -1 ). DETAILED DESCRIPTION
[0057] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0058] 1. Material preparation method
[0059] (1) Preparation of graphene / terbium composite materials
[0060] First, graphene and Tb 3+ (i.e. Tb molecules) were dispersed in anhydrous ethanol at a mass ratio of 10:1 and subjected to ultrasonic treatment for 30 minutes. After the ultrasonic treatment, the mixture was stirred on a stirrer and the above experiment was repeated twice to mix the two substances evenly. The evenly mixed mixture was dried to obtain Gh-Tb 3+ The composite catalyst (Gh in this application document refers to N-doped graphene) is placed in a tube furnace and heat treated at 300°C for half an hour. By adjusting the gas environment, catalysts containing Tb of different valence states can be obtained (the sample treated in air environment is Gh-Tb 3+ / 4+ , the sample treated in oxygen environment is Gh-Tb 4+ ).
[0061] (2) Preparation of nanocarbon / sulfur composites
[0062] Sulfur-filled (CNTs-S) composites were prepared by a typical melt-diffusion method. Usually, CNTs and sulfur powder are ground evenly in a mass ratio of 1:4 and then dispersed in CS2 to form a mixed solution. Next, the mixed solution is stirred at room temperature, and the mixed slurry is air-dried until CS2 is completely evaporated, and then heated at 155°C for 12 h. After cooling to room temperature, the CNTs-S composite material is obtained after grinding. In this study, the sulfur content of the CNTs-S composite material was controlled at 75-80 wt%.
[0063] (2) Preparation of nanocarbon / sulfur / graphene / terbium composite positive electrode
[0064] The nanocarbon / sulfur composite material, binder (such as polyvinylidene fluoride, PVDF), and conductive additive obtained above are mixed and dispersed in an organic solvent (NMP) at a mass ratio of 8:1:1, and coated on aluminum foil and placed in a 55°C oven for drying. Then, a layer of graphene / terbium composite interlayer prepared above is inserted on the upper layer of the dried positive electrode sheet. The preparation of the interlayer is to uniformly disperse the graphene / terbium composite material in an organic solvent (NMP) for ultrasonication, and then coated on the dried positive electrode sheet, and placed in a 55°C oven for further drying. Cut into circular pieces with a diameter of 14 mm to obtain CNT-S / Gh-Tb x+ Composite cathode. The sulfur loading of the cathode is controlled at 1-1.2 mg cm −2 .
[0065] 2. Battery Assembly and Electrochemical Measurements
[0066] CR2025 coin cell using CNTs-S / Gh-Tb x+ (x = 3, 3+ / 4, 4) or CNTs-S / Gh cathode, Li anode, Celgard 2400 separator and conventional electrolyte (1% LiNO3, 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solution of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) (1:1, v / v)) were assembled in an Ar-filled glove box (<0.1 ppm O2, H2O, Universal, MIKROUNA). The surface density is ~1.0 mg cm -2 and ~4.1 mgcm -2 The sulfur electrode with electrolyte / sulfur (E / S) controlled at ~15 μL mg -1 Considering the accuracy of the results, 8 batteries were prepared and tested under the same operating conditions. Cyclic voltammetry test (CV, voltage range: 1.6-2.8 V (vs. Li / Li + ), scan rate: 0.1 mV s -1 ) and electrochemical impedance spectroscopy (EIS, frequency range: 0.01 Hz-200 KHz, AC voltage amplitude: 5 mV) were measured at room temperature on an electrochemical workstation (CHI 760). The Neware CT-4008T-5V20mA-164 system was used to record the 1.6-2.8 V (vs. Li / Li + ) voltage range at different rates (1 C = 1675 mAh g -1 ) Cycle and constant current charge and discharge curves. Calculate the battery capacity based on the mass of positive sulfur in the lithium-sulfur battery.
[0067] 3. Performance Analysis
[0068] In order to predict the nature of the adsorption catalysis of LiPSs by Tb oxides with different valence states, the electronic structure of Tb oxides with different valence states was first calculated using density functional theory (DFT). Considering the inactive aggregation of Tb oxide catalysts in the SRR process and the conductivity of the catalyst system, N-doped graphene (marked as Gh in this application document unless otherwise specified) was introduced into the catalyst model construction ( Figure 1 ), in order to better anchor the catalyst and improve the electron transport of the system. Among them, four Tb atoms are coordinated with different numbers of O atoms to obtain three Tb valence states (Tb 3+ , Tb 3+ / 4+ and Tb 4+ Coordinate 6, 7 and 8 O atoms respectively). Figure 2 As shown, Gh-Tb 3+ of f The center of the belt is relatively high, according to d -Electron theory shows that it has stronger ability to provide electrons to the external circuit and adsorb external substances, forming Tb 3+ electron source. Similarly, low f Gh-Tb with center 4+ It is easy to accept electrons from the outside world and has a weak adsorption ability to the adsorbate, forming Tb 4+ Electron drain source. In contrast, Gh-Tb 3 + / 4+ Among the three composite materials, f The center of the band indicates that its adsorption of adsorbed molecules (such as LiPSs) is mild and the ability to gain and lose electrons is balanced (i.e., the generation of electron reservoirs (source and drain)). f The results of the band center obtained the binding energy calculation between the material and LiPSs ( E b ) with strong support. Figure 3 and Figure 4 In a, it can be seen that the sulfide molecules are adsorbed on the Gh-Tb 3+ / 4 + surface, and Gh-Tb 3+ / 4+ Compared with the other three materials (Gh-Tb 3+ , Gh-Tb 4+ , Gh) for most LiPSs (Li2S n , n = 8, 4, 1) clusters have a milder adsorption intensity overall. This means that Gh-Tb 3+ / 4+As an electron reservoir, it can not only effectively anchor dissolved LiPSs, but also enable the subsequent catalytic conversion of LiPSs to reach a reasonable level. The possible reaction process of the Gibbs free energy barrier on the catalyst surface was simulated by DFT, such as Figure 4 b) The reduction of S8 to Li2S8 is a spontaneous exothermic reaction on all substrates. 3+ It is an exothermic reaction. Although in Gh-Tb 3+ / 4+ The reaction is endothermic on the substrate, but in Gh-Tb 3+ / 4+ The Gibbs free energy barrier on Gh-Tb 4+ and Gh are relatively small (0.29 eV for Li2S8 to Li2S6, 0.12 eV for Li2S6 to Li2S4). 4+ The Gibbs free energy barrier for the formation of short-chain Li2S on the substrate (-0.69 eV Gh-Tb 4+ and 0.31 eV Gh-Tb 3+ / 4+ ) is much lower than Gh-Tb 3+ (1.65 eV) and Gh (1.083 eV), so it can be determined that Tb 3+ and Tb 4+ The Gibbs free energy barriers of the long-chain LiPSs conversion reaction and the short-chain LiPSs conversion reaction can be effectively reduced respectively. Considering that the Gibbs free energy barriers of each step are generally low, especially the lowest value of 0.12 eV in the step from Li2S6 to Li2S4, the entire sulfur conversion process from S8 to Li2S in the Gh-Tb 3+ / 4+ From the perspective of electron transfer, we infer that Tb 3+ The electron source can spontaneously provide electrons to the long-chain LiPSs, firmly capture the long-chain LiPSs and quickly convert them into short-chain sulfur species; then, driven by the discharge process, the Tb that serves as the electron storage 4+ The electron leakage continues to convert short-chain sulfur species into discharge products based on the principle of weak adsorption and strong catalysis, promoting the continuity of the sulfur reduction reaction. 3+ and Tb 4+ coexistence, in Tb 3+ / 4+ The electron transfer and electrochemical reaction on the electron reservoir (electron source and electron drain) are more efficient. Through DFT calculation research, it is believed that Gh-Tb 3+ / 4+ Due to the medium f It has the ability to gain and lose electrons and can capture LiPSs through the Tb-S bond with appropriate forces without affecting the subsequent catalytic conversion process of LiPSs, which is expected to improve the electrochemical performance of lithium-sulfur batteries.
[0069] We prepared three graphene-terbium composites (Gh-Tb 3+ , Gh-Tb 3+ / 4+ and Gh-Tb 4+ ) and characterized its structure. In the experiment, the tris(acetylacetonato)(1,10-phenanthroline)terbium(III) molecule ( Figure 5 a, hereinafter referred to as Tb molecules) as the source of Tb and N, and different methods including physical sonication, high temperature (300 °C) in air or O2 atmosphere, and the critical temperature of mass loss obtained by thermogravimetric analysis (TGA) data ( Figure 5 b) calcined and modified onto conventional Gh to form Gh-Tb with different valence states of Tb x+ Complex; overall comprehensive strategy such as Figure 6 shown.
[0070] The three Gh-Tb x+ Surface composition of the composites. Gh-Tb prepared by heat treatment under air conditions x+ Tb 3 composites d XPS data ( Figure 7 a) indicates that Tb 3+ (1276.0 / 1240.5 eV) content is 46.2%, Tb 4+ The content of (1278.2 / 1243.7 eV) is 53.8%, which indicates that mixed-valence Tb is formed, that is, Gh-Tb 3+ / 4+ . Uncalcined Gh / Tb Tb 3 d Only Tb in the spectrum 3+ The peak (1276.5 / 1240.7 eV) appears and Gh-Tb is formed. 3+ . The Gh-Tb prepared under O2 atmosphere x+ Tb 3 composites d The spectrum is mainly Tb 4+ The peak (1277.8 / 1243.0 eV) is the formation of Gh-Tb 4+ It is worth noting that the Gh / Tb molecular system (Gh-Tb 3+ / 4+ , Gh-Tb 4+ )N 1 s XPS spectra ( Figure 7 b) The presence of pyridine / pyrrole N peaks indicates that N-doped Gh is formed after thermal decomposition of Tb molecules containing N elements. In order to control the valence state of Tb to a single variable, in the next study, we will use N-doped Gh to prepare physically mixed Gh-Tb 3+and Gh reference samples.
[0071] From the TEM micrograph, it can be seen that Gh-Tb 3+ and Gh-Tb 4+ The Tb molecules and Tb oxide particles in the composite material will be micro-aggregated and unevenly dispersed on the layered Gh ( Figure 8 ad), while Gh-Tb 3+ / 4+ The TEM micrograph shows that the Tb oxide particles are well distributed and cover the entire surface of Gh ( Figure 8 ef). The Gh-Tb 3+ / 4+ A closer look at the complex revealed that Tb oxide existed in ultrafine clusters ( Fig. 9 ). Gh-Tb 3+ / 4+ Energy dispersive X-ray spectroscopy (EDX) elemental mapping ( Fig.10 ) further confirmed that C, N, O and Tb elements coexist homogeneously in the structure, which is consistent with the XPS results ( Fig.11 Inspired by the high conductivity and large active surface area of N-doped Gh, Tb with a unique electronic structure 3+ / 4+ Combining the excellent effects of LiPSs adsorption and catalysis, we used Gh-Tb 3+ / 4+ As a modified intercalation membrane for the positive electrode of lithium-sulfur batteries, it can promote SRR kinetics and alleviate the shuttle effect of lithium-sulfur batteries. Inspired by the high conductivity and large active specific surface area of N-doped Gh, combined with Tb 3+ / 4+ The unique electronic structure of Gh-Tb has excellent potential in LiPSs adsorption and catalysis. 3+ / 4+ It can be applied to the positive electrode modification of lithium-sulfur batteries to alleviate the shuttle effect of lithium-sulfur batteries. 3+ / 4+ As an intercalation film structure for modified positive electrode ( Fig.12 ), to improve the performance of lithium-sulfur batteries.
[0072] We added Li2S6 solution (2 mL, 0.25 mmol L -1 ) were added with equal amounts (5 mg) of Gh (i.e., N-doped Gh), Tb molecules, and Gh-Tb 3+ / 4+ The composite was visualized and Li2S6 adsorption experiments were performed, such as Fig.13 Obviously, the yellow Li2S6 solution with Gh added turned into light brown after 12h of static adsorption ( Fig.13(ii)). From the nitrogen adsorption-desorption isotherm of Gh, it can be seen that Gh has a certain physical adsorption capacity for LiPSs mainly due to its large porosity, in addition to a small part of the adsorption capacity contributed by limited N doping. However, the physical adsorption strength of the material is limited and cannot effectively capture LiPSs. In contrast, the chemical adsorption of Tb molecules has the advantage of anchoring a large number of LiPSs and can promote the subsequent sulfur-catalyzed conversion to proceed smoothly, resulting in a light yellow solution ( Fig.13 (iii)). Due to the physical and chemical synergy with LiPSs, the addition of Gh-Tb 3+ / 4+ The color of the Li2S6 solution of the sample turned almost colorless ( Fig.13 (iv)), although Gh-Tb 3+ / 4+ The specific surface area and mesopore volume are smaller than Gh ( Fig.14 ).
[0073] Gh-Tb before and after adsorption of Li2S6 solution 3+ / 4+ The samples were tested by XPS. Fig.15 As shown in a, Gh-Tb before adsorption of Li2S6 solution 3+ / 4+ There are two pairs of Tb 3 at 1240.4 / 1275.7 eV and 1243.2 / 1277.9 eV d peaks, respectively, attributed to Tb 3 + and Tb 4+ After adsorption of Li2S6 solution, these peaks obviously shifted to the direction of higher binding energy (Tb 3+ 1240.6 / 1276.1eV, Tb 4+ 1243.8 / 1278.5 eV), indicating that the electron cloud density around Tb atoms is reduced. The S 2 p In the XPS spectrum ( Fig.15 b) A pair of peaks are shown in the high binding energy region between 169 eV and 170 eV, corresponding to the sulfate species formed by the oxidation of sulfur solution in air. Compared with the Gh sample, the Gh-Tb 3+ / 4+ The S−S bond of the composite material is stronger at 164.1 / 165.2 eV, and an additional pair of new peaks appear at 162.6 / 163.7 eV corresponding to the chemical bond (S−M) formed between sulfur and metal. The above results show that Gh-Tb 3+ / 4+ It maintains good chemical affinity with LiPSs. s The stronger Li∙∙∙N peak at 54.5 eV also confirms that Gh-Tb 3+ / 4+The interaction between LiPSs ( Fig.15 c), and also illustrates that a “lithium bond”-like structure is formed between N-doped Gh and LiPSs.
[0074] In general, Gh-Tb 3+ / 4+ The formation of Tb−S and N∙∙∙Li bonds between LiPSs is very beneficial for chemical confinement of LiPSs, thereby effectively suppressing the shuttle effect, which is consistent with the binding energy calculation results ( Figure 4 a). Based on this good premise, CNTs-S / Gh-Tb 3+ / 4+ The cathode was compared with other cathodes, and its influence on the conversion kinetics of LiPSs, including liquid-liquid and liquid-solid conversion, was studied in depth.
[0075] Evaluation of heterogeneous SRR adsorption kinetics ( Fig.15 a) Gh-Tb 3+ / 4+ High-resolution Tb 3 before and after adsorption in Li 2 S 6 solution d XPS spectra ( Fig.15 b) Gh and Gh-Tb 3+ / 4+ S 2 after interaction with Li2S6 p XPS spectrum ( Fig.15 c) Li2S6 electrolyte as active ingredient, CNTs / Gh-Tb 3+ / 4+ 、CNTs / Gh-Tb 4+ 、CNTs / Gh-Tb 3+ The symmetric cell with Gh as electrodes at 30 mV s -1 CV curves at scan rate ( Fig.16 a) In CNTs / Gh-Tb 3+ / 4+ 、CNTs / Gh-Tb 4+ 、CNTs / Gh-Tb 3+ Current-time curves of Li2S deposition on the positive electrode and CNTs / Gh. The light yellow and green areas represent the reduction of Li2S8 and Li2S6, respectively, and the precipitation of Li2S is represented by gray, blue, yellow or red. Fig.16 b) CNTs-S / Gh-Tb 3+ / 4+ 、CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3+ The second cycle charge-discharge curve of the CNTs-S / Gh positive electrode GITT test (current 0.05C, pulse 10 minutes, relaxation 2 hours) ( Fig.16 c) D of the four cathodes in each reaction step Li+ Four positive electrode batteries in ( Fig.29 a) discharge and ( Fig.29b) Distribution of activation energy for the charging SRR process.
[0076] Using the same electrode pair (CNTs / Gh-Tb 3+ / 4+ 、CNTs / Gh-Tb 4+ 、CNTs / Gh-Tb 3+ and CNTs / Gh) and Li2S6 electrolyte, and the four samples were evaluated in soluble LiPSs (Li2S n , 4 < n≤8) in the initial liquid-liquid conversion process. -1 All cyclic voltammetry (CV) curves of terbium-containing batteries show two pairs of redox peaks (a / a0 and b / b0) at scan rates, indicating that terbium has reliable electrocatalytic activity for LiPS conversion ( Fig.16 a). Gh-Tb 3+ Symmetrical cells and Gh-Tb 4+ Compared with the symmetric cell (-0.07 V / 0.56 V), it exhibits a more positive reduction potential (-0.05 V) when sulfur is converted to Li2S6 and a lower oxidation potential (0.54 V) when Li2S6 is converted to S8. 3+ It has advantages in promoting the conversion of soluble long-chain LiPS. 3+ / 4+ The smallest reaction polarization, the highest redox current response, and the most obvious redox peak of the symmetric cell all confirm f Orbital regulation indeed brings strong electrocatalytic activity to the conversion between soluble LiPSs. Similar results were obtained by electrochemical impedance spectroscopy (EIS) tests on symmetric batteries of four electrode materials. Fig.17 As shown, containing Tb 3+ The symmetrical battery exhibits significantly lower charge transfer resistance (R ct , Table 1), especially CNTs / Gh-Tb 3+ / 4+ Symmetrical battery R ct The lowest, indicating that its charge transfer is the fastest, thus promoting SRR.
[0077]
[0078] In order to explore the LiPSs (Li2S n , n ≤ 4) to Li2S liquid-solid conversion process, constant potential nucleation experiment was carried out at 2.04 V using button cells containing Li2S8 electrolyte, and it was expressed as an It curve. The specific capacity of Li2S deposition was calculated according to Faraday's law (see Fig.16 b). Overall, CNTs / Gh-Tb3+ / 4+ The electrode and the other three electrodes (CNTs / Gh-Tb 4+ 5595 s, 0.37 mA, 283 mAh g -1 ; CNTs / Gh-Tb 3+ 4730 s, 0.36 mA, 229 mAh g -1 ;CNTs / Gh 7430 s, 0.22 mA, 197 mAh g -1 ) showed the fastest Li2S nucleation response rate (3604 s), the largest response current density (0.45 mA), and the highest Li2S deposition specific capacity (351 mAh g -1 ), indicating that in CNTs / Gh-Tb 3+ / 4+ The surface accelerated the Li2S deposition kinetics. Then, the cell was charged at a constant voltage of 2.35 V to study the conversion of Li2S to LiPSs (Li2S n , n≤4) oxidation process, namely Li2S decomposition test. Fig.16 As shown in c, CNTs / Gh-Tb 3+ / 4+ The electrode showed similar experimental phenomena to Li2S nucleation in the Li2S decomposition experiment, with the earliest Li2S decomposition response (7864 s), the largest oxidation current density (0.6 mA), and the highest Li2S decomposition specific capacity (621 mAh g -1 The parameters of the other three electrodes are (CNTs / Gh-Tb 4+ 7575 s, 0.55 mA, 586 mAh g -1 ; CNTs / Gh-Tb 3+ 8800 s, 0.36 mA, 397 mAh g -1 ;CNTs / Gh 14259 s, 0.19 mA, 327 mAh g -1 ), showing Tb 3+ / 4+ The best catalytic ability for Li2S oxidation kinetics. It is worth noting that CNTs-S / Gh-Tb 4+ The cathode exhibited the second best performance during Li2S deposition and decomposition, which means that Tb 4+ It can well promote the conversion of short-chain LiPS (liquid-solid / solid-liquid conversion).
[0079] Similar results were also confirmed by the potentiostatic intermittent titration technique (PITT) and the galvanostatic intermittent titration technique (GITT), both of which were performed in actual working lithium-sulfur button cells rather than in an ideal Li2S8 solution. In the PITT experiment, the assembled cells were discharged from the open circuit voltage to 1.6 V at 2 mV intervals. Fig.18 a shows the relationship between the current response and the voltage pulse. When the test voltage is above 2.1 V, the addition of Tb 3+ / 4+ The strong current caused by the constant voltage discharge in each step increased by about 153.6%, and then the current dropped rapidly in a very short time (~16 s), indicating that Tb 3 + / 4+ The presence of CNTs-S / Gh-Tb changes the electrochemical kinetic equilibrium and improves the conversion of the liquid-liquid process. The deposition behavior of Li2S on the positive electrode surface was studied between 2.1-2.0 V. 3+ / 4+ The Li2S deposition rate of the battery is faster and the response current density is larger, 0.41 mA cm -2 , which is lower than the Li2S deposition response current density of CNTs-S / Gh battery of 0.27 mA cm -2 52% higher. In addition, CNTs-S / Gh-Tb 3+ / 4+ The Li2S deposition capacity (705.3 mAh g -1 ) also reached the control sample CNTs-S / Gh (607.3 mAh g -1 ), which again shows that CNTs-S / Gh-Tb 3+ / 4+ Similar kinetic advantages are found in liquid-solid transformation processes.
[0080] GITT was used to further monitor Li + The transmission behavior of Li + The transport capacity is a key descriptor affecting the liquid-solid conversion kinetics. The discharge process is compared with the other three cathodes. Fig.18 b It can be seen that CNTs-S / Gh-Tb 3+ / 4+ The second discharge platform of the positive electrode Li-S battery in GITT mode is longer and the voltage fluctuation is smaller, especially in region III (~2.1 V) where soluble LiPSs transform to solid Li2S2 / Li2S. The GITT analysis of the charging process shows that a large voltage fluctuation is observed in the initial solid-solid conversion process (from Li2S to Li2S2) of all electrodes, indicating the existence of slow kinetic behavior and the CNTs-S / Gh-Tb in the solid-liquid conversion step. 3+ / 4+ The positive electrode voltage fluctuation is reduced to the maximum, and the overpotential is kept very small during liquid-liquid conversion.+ Diffusion coefficient ( ), as shown in formula (1): (1)
[0081] Where m B 、V M 、M B are the mass, molar volume, and molecular weight of the active substance, respectively; is the duration of the current pulse (600 s), A is the surface area of the active material, is the change in steady-state voltage due to the pulse, is the voltage change of constant current discharge. Fig.18 c shows that in CNTs-S / Gh-Tb 3+ / 4+ of Compared with other batteries, it has been improved by an order of magnitude, especially from liquid Li2S4 to solid Li2S2 / Li2S, which confirms that CNTs-S / Gh-Tb 3+ / 4+ In promoting + The best function in terms of diffusion and activation lithiation kinetics. In steps I and II, CNTs-S / Gh-Tb 3+ of CNTs-S / Gh-Tb 4+ In steps III and IV, CNTs-S / Gh-Tb 3+ of CNTs-S / Gh-Tb 4+ Small. Confirmed that Tb 3+ and Tb 4+ Active roles in liquid-liquid transition (long-chain LiPSs) and liquid-solid transition (short-chain LiPSs), respectively.
[0082] The EIS spectra at different potentials and temperatures during the charge and discharge process were experimentally determined ( Figure 19-26 ), and use Fig.28 After fitting the equivalent circuit in the analysis ( Fig. 27 ). It can be seen that during the discharge process ( Fig.29 a) E a It is low in the long-chain LiPSs conversion and formation stage (2.8-2.4 V), gradually increases in the short-chain LiPSs formation stage (2.4-2.1 V), and finally reaches the maximum value in the most difficult insoluble product formation stage (2.0-1.7 V). It can be clearly seen during the charging process. E a The reverse trend of Fig.29 b). The entire discharge process is within the voltage range of long-chain LiPSs conversion (2.8-2.1 V), Tb 3+ SampleE a Less than Tb 4+ samples, while in the voltage range of short-chain LiPSs conversion, Tb 4+ The Ea of the sample is lower. The charging process also shows similar results. 4+ The battery has a relatively low conversion voltage (about 2.3 V) in short-chain LiPSs. E a and a larger E a Change rate, while CNTs-S / Gh-Tb 3+ The battery conversion voltage of long-chain LiPSs (2.4 V) E a The above results again show that Tb 3+ and Tb 4+ They promote the conversion of long-chain and short-chain LiPSs respectively. 3+ / 4+ The activation energy of the battery at each step of the charge / discharge process E a The values are relatively low, which again shows that Tb 3+ / 4+ It can reduce the energy barrier in the sulfur conversion process, significantly accelerate the sulfur bidirectional conversion kinetics and significantly improve the sulfur utilization rate, which is expected to improve battery performance.
[0083] Semi-in-situ XPS was used to study the action mechanism of different catalysts. Fig.30 As shown in (ad), according to the literature reports, S 2 at 169.4 / 170.6 eV and 167.2 / 168.6 eV p The peaks can be attributed to the characteristic peaks of lithium salt (LiTFSI) and sulfite produced by the decomposition of LiTFSI. p The spectrum can be fitted to obtain four different characteristic peaks, namely S8 at 164.0 / 165.3 eV, long-chain LiPSs (Li2S n , 4 ≤ n ≤ 8), 161.68 eV short chain L2S2 and 160.21 eV Li2S. In the fully charged state (2.8 V), the surface composition of all positive electrodes is mainly S8. When the battery is discharged to 2.0 V, in the case of Tb 3+ The positive electrode (CNTs-S / Gh-Tb 3+ / 4+ and CNTs-S / Gh-Tb 3+ ), the S8 signal significantly weakens the long-chain LiPSs (Li2S n , 4 ≤ n ≤8) is significantly enhanced, indicating that Tb 3+It has a good catalytic effect on the conversion of S8 to long-chain LiPSs. At the end of discharge (1.6 V), the peak intensity of Li2S2 / Li2S is higher than that of Tb 4+ The positive electrode (CNTs-S / Gh-Tb 3+ / 4+ and CNTs-S / Gh-Tb 4+ ) than without Tb 4+ The positive electrode (CNTs-S / Gh-Tb 3+ and CNTs-S / Gh) are stronger, and contain Tb 4+ There are still some long-chain LiPSs (Li2S n , 4 ≤ n ≤8) is not completely converted, indicating that Tb 4+ The conversion between long-chain LiPSs is limited, but it can effectively catalyze the conversion of short-chain LiPSs to Li2S2 / Li2S. This phenomenon is also highly reversible during the charging process. Fig.30 (ad) shows that in the presence of Tb 4+ The positive electrode (CNTs-S / Gh-Tb 3+ / 4+ and CNTs-S / Gh-Tb 4+ ), after charging to 2.4 V, the short-chain Li2S2 / Li2S is more easily converted into long-chain LiPSs (Li2S n , 4 ≤ n ≤ 8); when the battery is charged to 2.8 V in the presence of Tb 3+ The positive electrode (CNTs-S / Gh-Tb 3+ / 4+ and CNTs-S / Gh-Tb 3+ ), long-chain LiPSs (Li2S n , 4 ≤ n ≤ 8) has a higher conversion efficiency to S8.
[0084] In situ UV-vis spectroscopy of the electrode / electrolyte interface ( Fig.31 ,32) and the qualitative analysis of their corresponding absorbance intensity ( Fig.33 ) further supports this statement, compared with the Tb-free 3+ The positive electrode (CNTs-S / Gh-Tb 4+ Compared with CNTs-S / Gh), 3+ The positive electrode (CNTs / Gh-Tb 3+ / 4+ and CNTs / Gh-Tb 3+ ) During the discharge process S8 2- / S4 2- The intensity decreases faster, while S3 *- The corresponding increase in the free radical signal once again confirmed that Tb 3+It tends to accelerate the conversion of long-chain LiPSs to short-chain LiPSs. 3+ Positive at ~2.3 V - 2.8 V during S4 2- / S6 2- The change of the signal further proves the above-mentioned point of view. 4+ Positive S3 *- The absorption intensity of free radicals continues to decrease, and at the same time, Tb 4+ (CNTs-S / Gh-Tb 3+ / 4+ and CNTs-S / Gh-Tb 4+ ) of the positive electrode, S3 2- The absorbance intensity of S4 is rapidly decaying. 2- / S6 2- The absorption intensity of Tb increases with the progress of charging, which again indicates that 4+ It can promote the conversion of short-chain LiPSs. 3+ / 4+ The optimal conversion to long-chain and short-chain LiPSs during discharge / charge is attributed to Tb 3+ and Tb 4+ Electronic structure coupling occurs again.
[0085] In situ Raman spectroscopy was used to analyze the conversion pathways of LiPSs on different sulfur-containing cathodes in real time. Fig.34 In a and b, the S8 species on the surface of CNTs-S / Gh cathode are at 154, 219 and 473 cm -1 There are three obvious peaks at 1.6 V, and the intensity of S8 gradually decreases when the electrode is fully discharged to 1.6 V. However, due to the limited catalytic ability of CNTs-S / Gh, no signal indicating the generation of short-chain LiPSs appears during the whole process. 3+ ( Fig.34 c, d) and CNTs-S / Gh-Tb 4+ positive electrode( Fig.34 e,f) show the S8 conversion similar to that of CNTs-S / Gh; in addition, CNTs-S / Gh-Tb 3+ When the positive electrode is discharged to about 2.2 V, the -1 There are two weak peaks corresponding to S5 2- and S3 2- +S4 2- Signal; CNTs-S / Gh-Tb 4+ The positive electrode is discharged to about 2.1-2.0 V at 447 cm -1S4 appeared 2- +Li2S2 signal, indicating that Tb 3+ and Tb 4+ They play a role in promoting the conversion of long-chain and short-chain LiPSs, respectively. 3+ / 4+ positive electrode( Fig.34 g, h). In addition to the gradual weakening of the S8 signal as the discharge progresses, an obvious S6 signal appears when the discharge reaches the intermediate state (2.3-2.2 V). 2- and S5 2- signal, further discharge until the end with S6 2- and S5 2- The signal weakened and the signal of Li2S2 appeared and gradually strengthened. The above results show that S8 passes through S6 2- / S5 2- / S4 2- The intermediate state has a unique transformation pathway to Li2S / Li2S2. Figure 4 ) may be due to the formation of a new Li2S5 intermediate, which acts as a springboard for the conversion of Li2S6 to Li2S4.
[0086] 4. Evaluation of the electrochemical performance of the battery
[0087] Thermogravimetric analysis showed that the sulfur content of the electrode sheet used to assemble the battery was 78 wt% ( Fig.35 ). The catalyst loading was controlled below 0.7 wt% to avoid affecting the sulfur content of the cathode. A mass ratio of Tb molecules to Gh in the cathode of 1:10 was shown to be optimal for battery performance ( Fig.36 ). First, for conventional sulfur content of about ~1.0 mg cm -2 The battery is evaluated.
[0088] from Fig.37 and Fig.38 From the CV graphs of the four batteries in a, there are two reduction peaks at around 2.3 V and 2.0 V during the discharge process, corresponding to the conversion of solid sulfur (S8) to long-chain LiPSs (Li2S n , 4 ≤ n ≤ 8, P1), and then to the two-step reduction reaction of short-chain Li2S2 / Li2S (P2). In addition, the broad continuous oxidation peak at ~2.4 V during the charging process corresponds to the process of oxidation from Li2S2 / Li2S to LiPSs (P3) and then to S8 (P4). CNTs-S / Gh-Tb 3+ / 4+ The CV curves of the battery almost overlap in subsequent cycles after initial activation, which means that the battery reaction has better reversibility.4+ 、CNTs-S / Gh-Tb 3+ Compared with CNTs-S / Gh batteries, CNTs-S / Gh-Tb 3+ / 4+ The separation between the P2 and P3 peaks of the cell is minimal ( Fig.38 b), which means adding Tb 3+ / 4+ The resulting battery has minimal electrochemical polarization and optimal electrochemical kinetics. 3+ / 4+ The most positive reduction onset potential and the most negative oxidation onset potential of the battery indicate that CNTs-S / Gh-Tb 3+ / 4+ The cell has the lowest energy barrier for sulfur conversion and the lowest resistance to redox reactions, which is consistent with the activation energy results ( Fig.29 ) and the results of electrochemical impedance spectroscopy (EIS) are in good agreement ( Fig.17 ), compared with other batteries CNTs-S / Gh-Tb 3+ / 4+ The charge transfer resistance of the battery (R ct ,See Fig.39 ) and electrolyte resistance (R e , see Fig.40 ) is the lowest. During battery charging and discharging, the electrolyte resistance (R e ) corresponds to the maximum value of lithium polysulfide (Li2S n ) concentration peak, and the subsequent decrease in electrolyte resistance is related to the further conversion of polysulfides leading to a decrease in their concentration. 3+ / 4+ Battery R e is the smallest, these results show that Tb 3+ / 4+ The successful confinement and catalytic conversion of polysulfides. The same phenomenon also occurs during charging, and R e The peak starts to decrease earlier in potential, which further proves the improved reaction kinetics.
[0089] In order to quantitatively evaluate the effect of catalysis on the sulfur conversion kinetics, the Tafel slope was calculated based on the reduction peak and oxidation peak in the CV curve. Fig.41 As shown in Figure 5, the Tafel slope values at P1, P2, and P3 increased from 107, 99, and 103 mV dec on the CNTs-S / Gh electrode. -1 Down to 96, 91 and 76 mV dec -1 (CNTs-S / Gh-Tb 3+ electrode), then to 72, 59 and 65mVdec -1 (CNTs-S / Gh-Tb 4+ electrode). Importantly, Tb 3+ / 4+The addition of further reduced the Tafel slope of the peak to the lowest values (65, 42, and 60 mV dec -1 , corresponding to the P1, P2, and P3 peaks, respectively), indicating a 42–60% enhancement in the kinetics of each sulfur redox step conferred by the selective acceleration engineering.
[0090] according to Fig.43 a and Fig.42 The constant current discharge / charge curves at different rates in the discharge and charge curves correspond to the reduction and oxidation reaction processes of the lithium-sulfur battery, which is consistent with the redox peak in the CV results ( Fig.38 ) is in good agreement. It is worth noting that due to the faster electron / ion transfer rate of LiPS conversion, the voltage polarization is aggravated at a relatively high rate (2 C), and the discharge / charge platform is unstable. The charge-discharge platform curve of the second cycle at 0.2 C is taken as an example for in-depth analysis ( Fig.43 a), CNTs-S / Gh-Tb 3+ / 4+ The voltage polarization of the battery is as small as ΔE = 18 mV (the voltage polarization value is represented by the gap between the discharge and charge curves), and the first plateau Q at about 2.3 V up Capacity value is 392 mAh g -1 Close to the theoretical capacity (418 mAh g -1 ), compared with the other three batteries, the second platform (Q low ) was extended by 24%, indicating that it has a higher utilization rate of active sulfur and a faster liquid-liquid conversion, Gh-Tb 3+ / 4+ The special catalytic effect of Li2S accelerates the Li2S deposition and liquid-solid transformation kinetics.
[0091] CNTs-S / Gh-Tb 3+ / 4+ The battery exhibits the best rate performance ( Fig.44 ). Not only at 0.2, 0.5, 1 and 1.5 C (1 C = 1675 mA g -1 ) can achieve 1522, 1063, 980 and 944 mAh g -1 Excellent discharge capacity, even at a current density of 2 C, can reach 880 mAh g -1 High discharge specific capacity. It is better than CNTs-S / Gh-Tb 4+ (The discharge specific capacities at 0.2, 0.5, 1, 1.5, and 2 C are 1464, 979, 828, 732, and 617 mAh g -1 ), CNTs-S / Gh-Tb 3+(The discharge specific capacities at 0.2, 0.5, 1, 1.5, and 2 C are 1214, 848, 761, 665, and 560 mAh g -1 ) and CNTs-S / Gh (the discharge specific capacities at 0.2, 0.5, 1, 1.5 and 2 C were 1176, 795, 693, 607 and 507 mAh g -1 More importantly, when the rate is switched back to 0.2 C, the CNTs-S / Gh-Tb 3+ / 4+ Battery recoverable 1042 mAh g -1 The reversible specific capacity of the other batteries recovered to 981, 856, and 767 mAhg, respectively. -1 (corresponding to CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3+ and CNTs-S / Gh batteries), indicating that CNTs-S / Gh-Tb 3+ / 4+ The electrode has good structural stability at different rates.
[0092] CNTs-S / Gh-Tb 3+ / 4+ The battery has a sulfur loading of about 1.0 mg cm -2 Good long cycle performance can be achieved in the case of Fig.45 As shown in a. From CNTs-S / Gh-Tb 3+ / 4+ The electrode exceeded 1157 mAh g at 1 C rate -1 The initial discharge capacity of CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3 + The initial discharge specific capacities of CNTs-S / Gh and CNTs-S / Gh at 1 C are 906 mAh g -1 , 818 mAh g -1 , 596 mAh g -1 , the sulfur utilization rates were 50%, 48% and 49.36% respectively. As the cycles progressed, at the end of the 500th cycle, CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3+ and CNTs-S / Gh batteries suffer from rapid capacity decay due to the loss of active sulfur and the shuttle effect (their capacity retention rates are 45%, 46%, and 23%, respectively, and the capacity decay rates per cycle are 0.12%, 0.11%, and 0.15%, respectively). 3+ / 4+The battery capacity can be stably maintained at 656 mAh g after 500 cycles. -1 The above accounts for 56% of the initial capacity. Under the same test conditions, the capacity decay rate of each cycle is 0.087%. The cycle stability has been significantly improved, and the average Coulomb efficiency during the entire cycle is higher than 99%, indicating that soluble polysulfides can be successfully captured and their high sulfur utilization rate. 3+ / 4+ In the long cycle test at 0.5 C ( Fig.45 b) Provides about 1115 mAh g -1 The initial discharge capacity was 990 mAh g after 108 cycles. -1 , the capacity retention rate is as high as 89%.
[0093] High sulfur loading capacity is the key to expand the practical application of lithium-sulfur batteries, so we further increase the areal sulfur loading to 4.1 mg cm -2 like Fig.45 As shown in c, CNT-S / Gh-Tb 3+ / 4+ The high sulfur loading of the cathode exhibits good capacity retention, with an initial discharge specific capacity of 993 mAh g at 0.1 C. -1 After 120 cycles, the discharge capacity is 765 mAh g -1 , while CNTs-S / Gh-Tb 4+ 、CNTs-S / Gh-Tb 3+ The battery discharge capacity of the CNTs-S / Gh positive electrode significantly decays and cannot be stably cycled. This comparison further proves that Tb in high sulfur loading electrodes 3+ and Tb 4+ The importance of simultaneously participating as an electron reservoir to accelerate the discharge and charge process. Later, the use of Gh-Tb under harsh conditions was further studied. 3+ / 4+ The practicality of the catalyst battery was evaluated (electrode surface density was 5.2 mg cm -2 , E / S ratio was 7.5 μL mg -1 At 0.05 C ( Fig.45 d) Gh-Tb at discharge rate 3+ / 4+ The catalyst still enables lithium-sulfur batteries with a capacity of up to 1225 mAh g in lean electrolyte conditions. -1 The initial discharge specific capacity has a capacity decay rate of 0.18% after 134 cycles.
[0094] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A nanocarbon / sulfur / graphene / terbium composite positive electrode, characterized in that: The invention comprises terbium loaded on a graphene conductive substrate as a positive electrode modification layer, a CNTs-S composite material as a positive electrode sheet, and the terbium comprises Tb 3+ , Tb 4+ , Tb 3+ / 4+ .
2. The nanocarbon / sulfur / graphene / terbium composite positive electrode according to claim 1, characterized in that: The terbium is Tb 3+ / 4+ .
3. The method for preparing a nanocarbon / sulfur / graphene / terbium composite positive electrode according to claim 1, characterized in that: The following steps are involved: Step (1), graphene and Tb 3+ Evenly dispersed in anhydrous ethanol at a mass ratio of 1-15:1; Step (2), drying the mixed solution obtained in step (1) to obtain graphene-Tb 3+ The composite catalyst is placed in a tube furnace for heat treatment, and a graphene-terbium oxide composite material containing terbium in different valence states is obtained by regulating the gas environment; Step (3), preparing a CNTs-S composite material by a melt-diffusion method, and then mixing the CNTs-S composite material with a binder and a conductive additive to prepare a positive electrode sheet; Step (4), uniformly dispersing the graphene-terbium composite material in an organic solvent, coating the dried positive electrode sheet prepared in step (3), and then continuing to dry to obtain a graphene-terbium composite material interlayer; Step (5), inserting a layer of graphene-terbium composite material interlayer prepared in step (4) on the upper layer of the dried positive electrode sheet obtained in step (3) to obtain a nano-carbon / sulfur / graphene / terbium composite positive electrode.
4. The method for preparing a nanocarbon / sulfur / graphene / terbium composite positive electrode according to claim 3, characterized in that: In step (1), graphene and Tb 3+ The mass ratio is 10:
1.
5. The method for preparing a nanocarbon / sulfur / graphene / terbium composite positive electrode according to claim 3, characterized in that: In step (2), the temperature of the tube furnace is 280-320°C, and the graphene-Tb is obtained in an air environment. 3+ / 4+ ; The sulfur content of the CNTs-S composite material is controlled at 75-80wt%.
6. The method for preparing a nanocarbon / sulfur / graphene / terbium composite positive electrode according to claim 3, characterized in that: The binder in step (3) is polyvinylidene fluoride.
7. The method for preparing a nanocarbon / sulfur / graphene / terbium composite positive electrode according to claim 3, characterized in that: In step (4), the organic solvent is N-methylpyrrolidone; and the drying temperature of the oven is 50-60°C.
8. The method for preparing a nanocarbon / sulfur / graphene / terbium composite positive electrode according to claim 3, characterized in that: In step (5), the sulfur loading in the composite positive electrode is controlled at 1-1.2 mg cm -2 .
9. A high performance lithium-sulfur battery, characterized in that: It comprises the nano-carbon / sulfur / graphene / terbium composite positive electrode as described in any one of claims 1-2.